2023
DOI: 10.3390/su15108173
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Women’s Empowerment on the Corporate Environmental, Social, and Governance (ESG) Disclosure

Abstract: This research article examines the relationship between women’s empowerment and corporate ESG disclosure variables by analyzing 10,121 publicly traded companies listed worldwide with historical ESG data available in Bloomberg from 2016 to 2020. The paper seeks to answer whether corporate gender diversity directly affects companies’ ESG disclosure by using proprietary Bloomberg ESG disclosure scores and independent variables such as the female board and executive representation. Control variables, like the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
1
1
Order By: Relevance
“…This is reflected in the probability value recorded in the analysis, which exceeds the predetermined significance level limit, so the hypothesis cannot be rejected. This finding is a point of contrast with some previous reference studies, such as those mentioned in the works of Aabo et al (2023), Dempere et al (2023), Romano et al (2020), and Yadav et al (2023. Despite the difference in results, this study highlights the similarity with previous studies in terms of the generally positive value of the gender constant.…”
Section: Assumption Testcontrasting
confidence: 93%
“…This is reflected in the probability value recorded in the analysis, which exceeds the predetermined significance level limit, so the hypothesis cannot be rejected. This finding is a point of contrast with some previous reference studies, such as those mentioned in the works of Aabo et al (2023), Dempere et al (2023), Romano et al (2020), and Yadav et al (2023. Despite the difference in results, this study highlights the similarity with previous studies in terms of the generally positive value of the gender constant.…”
Section: Assumption Testcontrasting
confidence: 93%
“…Further, institutional quality plays a moderating role between these associations. A recent study suggested that corporate gender diversity directly spurs firm ESG disclosures that can lead to better corporate value [41]. In the context of Korea, ref.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%